Powerful outflows in the central parsecs of the low-luminosity active galactic nucleus NGC 1386 - Rodríguez-Ardila, Alberto; Luque, Rafael (Arxiv, 2017)
Low-luminosity Active Galactic Nuclei, i.e. L_bol/L_edd ~ 10^-6 - 10^-3, constitute the bulk population of Active Galactic Nuclei (AGNs). Powerful jets, common in these objects, are a crucial source of feedback energy driving mass outflows into the host galaxy and the intergalactic medium. This paper reports the first direct measurement of powerful mass outflows traced by the forbidden high ionization gas in the low luminosity AGN NGC1386 at scales of a few parsecs from the central engine. The high angular resolution of the data allows us to directly measure the location, morphology and kinematic of the outflow. This the form of two symmetrical expanding hot gas shells moving in opposite directions along the line of sight. The co-spatiality of the gas shells with radio emission seen at the same parsec scales and with X-rays indicates that this is a shock-driven outflow induced by an incipient core-jet. With a minimum number of assumptions, we derive a mass outflow rate of 11 solar masses/yr, comparable to those of powerful AGN. The result has strong implications in the global accounting of feedback mass and energy driven by a low-luminosity AGN into the medium and the corresponding galaxy evolution.